IMPACT OF PROLONGED USE OF ANTIDEPRESSANTS ON NEUROPLASTICITY - Pedro do Valle Varela, João; Roschy da Silva Costa, Vinicius; Sobrinho Vaz, Natália; Henrique de Melo Almeida, Thomas; Silva de Oliveira Bernardes, Gabriel; Rodrigues de Almeida, Letícia; Luiza Fonseca Maia Caetano, Ana; de Oliveira Figueiredo, Bruno (Health and Society, 2024)
Antidepressants are widely used in the treatment of depressive and anxiety disorders and are essential for the management of these conditions. However, the impact of prolonged use of these drugs on neuroplasticity - the brain’s ability to reorganize itself, forming new neural connections - has been a topic of growing interest and debate in the scientific community. This abstract addresses the effects of prolonged use of antidepressants on neuroplasticity, considering their implications for long-term mental health. The aim of this paper is to examine and synthesize the scientific evidence on the impact of long-term use of antidepressants on neuroplasticity, with a focus on how these changes can influence the effectiveness of treatment and the long-term prognosis of patients. This study conducts a literature review on the long-term effects of antidepressants on neuroplasticity, investigating both the therapeutic potentials and the associated risks. The review focuses on how neuroplasticity can influence treatment outcomes, tolerance to antidepressants, and the impacts on specific populations, such as the elderly and individuals with hormonal variations. Antidepressants, especially selective serotonin reuptake inhibitors (SSRIs) and serotonin and noradrenaline reuptake inhibitors (SNRIs), have been shown to influence neuroplasticity in several ways. Pre-clinical and clinical studies suggest that prolonged use of these drugs can promote neurogenesis, particularly in the hippocampus, an area of the brain crucial for memory and learning. This neurogenic effect is associated with an improvement in depressive symptoms and the brain’s ability to adapt to new challenges. In addition, antidepressants appear to increase the expression of neurotrophic factors, such as brain-derived neurotrophic factor (BDNF), which plays a vital role in the survival and growth of neurons. The increase in BDNF levels may contribute to the restoration of synaptic connectivity, which is often compromised in patients with depression. However, there is controversy about the long-term effects of continuous use of these drugs on neuroplasticity. Some studies suggest that, despite the initial benefits, prolonged use can lead to a “rigidity” in brain plasticity, making it difficult to adapt to new treatments or therapeutic strategies. In addition, the impact on other areas of the brain, such as the prefrontal cortex, which is involved in decision-making and emotional control, is still poorly understood and requires further research. These findings raise questions about the optimal duration of treatment with antidepressants and the need for continuous monitoring of patients’ long-term mental health. Neuroplasticity may be a crucial factor in individual response to treatment and the possibility of relapse or development of resistance to treatment. Therefore, the prolonged use of antidepressants has a significant impact on neuroplasticity, initially promoting neurogenic effects and an increase in synaptic connectivity, which can improve depressive symptoms. However, the long-term effects still need to be better understood, especially with regard to the possible “rigidity” in brain plasticity and the implications for ongoing treatment. To maximize the benefits and minimize the risks, it is essential that treatment with antidepressants is carefully monitored, with attention to changes in neuroplasticity over time. More research is needed to elucidate the underlying mechanisms and guide clinical practice towards more effective and safer strategies for the management of depression and other related disorders.